"A greatly unexplored area": Digital curation and innovation in digital humanities. (5th May 2017) - Poole, Alex H.
Abstract : New types of digital data, tools, and methods, for instance those that cross academic disciplines and domains, those that feature teams instead of single scholars, and those that involve individuals from outside the academy, enables new forms of scholarship and teaching in digital humanities. Such scholarship promotes reuse of digital data, provokes new research questions, and cultivates new audiences. Digital curation, the process of managing a trusted body of information for current and future use, helps maximize the value of research in digital humanities. Predicated on semistructured interviews, this naturalistic case study explores the creation, use, storage, and planned reuse of data by 45 interviewees involved with 19 Office of Digital Humanities Start‐Up Grant (SUG) projects. Interviewees grappled with challenges surrounding data, collaboration and communication, planning and project management, awareness and outreach, resources, and technology. Overall this study explores the existing digital curation practices and needs of scholars engaged in innovative digital humanities work and to discern how closely these practices and needs align with the digital curation literature.